Influence of penalty goals on the UEFA Champions League: an analysis of winning and losing teams - Souza, Gabriel Luis Franco Ruy de (2021)
Football has been constantly studied, mainly in the area of game analysis. Researchers seek to understand and study the sport and find solutions to break the line of defense adversary. Within these solutions, penalty goals stand out for their importance during the 90 minutes, resulting in some occasions in team victories. Thus, this study sought to analyze and compare the influence of penalty goals during the group phase of UEFA Champions League tournaments in the seasons from 2010 to 2020, relating the winning and losing teams with the teams classified and disqualified for the eliminatory phase of the competition. For this purpose, we analyzed the summaries of all 960 matches of the group phase of UEFA Champions League tournaments in the seasons cited, being counted only the matches that registered penalty goals. Thus, although there was a significant difference between the winning and losing teams (t158=3.289, p=0.001), there was no difference between the classified and disqualified teams (t211=1.479, p=0.141). Teams need a well-structured game model in order to enjoy the set ball. This way, from this game model, with variations of offensive and defensive actions, the penalty goals will be important, obtaining better performance rates.